2019
DOI: 10.20448/journal.501.2019.61.45.51
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion and Health Shocks: A Panel Data Analysis of 36 African Countries

Abstract: Numerous evidence has revealed that African countries lagged behind in the attainment of healthrelated targets of the recent past Millennium Development Goals (MDGs). Perhaps because most Africans depend largely on out-of-pocket payments for medical-care services during their health shocks experiences. Evidently, this has been a great concern to both citizens and policy makers across Africa for a long time. Therefore, this paper investigates the impact of financial inclusion on health shocks in 36 African nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…English as the language of more than half of the population of the world and understood well globally (Aydiner, Tatoglu, Bayraktar, Zaim, & Delen, 2019; Owan & Agunwa, 2019; Popoola, 2019;Puteri, 2018;Rahman & Amir, 2019). This importance of the English language (EL) has created a huge impact and this has become the major language of the internet and IT.…”
Section: The Mediating Role Of English Language Use In the Interrelation Between Application Contents And Business Marketing Performancementioning
confidence: 99%
“…English as the language of more than half of the population of the world and understood well globally (Aydiner, Tatoglu, Bayraktar, Zaim, & Delen, 2019; Owan & Agunwa, 2019; Popoola, 2019;Puteri, 2018;Rahman & Amir, 2019). This importance of the English language (EL) has created a huge impact and this has become the major language of the internet and IT.…”
Section: The Mediating Role Of English Language Use In the Interrelation Between Application Contents And Business Marketing Performancementioning
confidence: 99%
“…Firstly, to the best of our knowledge, this is still the first study to have investigated the role of education in moderating the effect of financial inclusion on healthcare in a panel data analysis that includes all 54 countries in Africa. The closest works to our study are those of Immurana et al (2021) and Popoola (2019). Both studies investigated the effect of financial inclusion on health performance in Africa by employing life expectancy and death rates as proxies of health.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the study analyzes the determinants of financial exclusion by introducing some factors of financial exclusion related to the various constraints faced by unbanked individuals (people who do not have accounts at formal financial institutions). Timothy (2019) used a panel data analysis and macrolevel data of 36 African countries to show that financial inclusion, measured by the number of depositors with commercial banks, is positively correlated with life expectation. Using time series analysis and macroeconomic data, Afolabi (2020) found that financial inclusion, measured by rural loans, the number of bank branches and level of liquidity, has a positive and significant effect on Nigeria's economic growth in the short and long runs.…”
Section: Introductionmentioning
confidence: 99%